2021
DOI: 10.1080/24705357.2021.1938256
|View full text |Cite
|
Sign up to set email alerts
|

Wake length of an artificial seagrass meadow: a study of shelter and its feasibility for restoration

Abstract: Wake length of an artificial seagrass meadow: a study of shelter and its feasibility for restorationSeagrasses are essential marine ecosystems for which restoration has proven challenging due to increased hydrodynamic stress. This study aims to analyze the flow alteration induced by an artificial seagrass (ASG) meadow by characterizing its wake effect through a shelter distance and thus yield guidance for seagrass restoration projects. Here, we define shelter distance as the longitudinal extent behind a meadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The major stress seems to be high solar radiation, although combined with salinity stress 56 . High mechanical disturbance inhibits the colonization of submerge plants near shoreline [57][58][59] . However, a large number of emergent plants were naturally colonized along the shoreline in decades ago, 60,61 and Phragmites australis colonies were widely recovered in some areas now.…”
Section: Discussionmentioning
confidence: 99%
“…The major stress seems to be high solar radiation, although combined with salinity stress 56 . High mechanical disturbance inhibits the colonization of submerge plants near shoreline [57][58][59] . However, a large number of emergent plants were naturally colonized along the shoreline in decades ago, 60,61 and Phragmites australis colonies were widely recovered in some areas now.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratory studies utilizing ASG to investigate the impact of submerged vegetation on the hydrodynamic regime (e.g., Nepf and Vivoni, 2000;Bouma et al, 2005) show that, by providing the sheltering capacity that is typically attributed to natural seagrass meadows, ASG mats, consisting of several leaves fixed to a base layer and thus mimicking a meadow section are an innovative approach to promote positive feedback mechanisms. Villanueva et al (2021) tested the extent of shelter behind ASG patches of different lengths and found that even with a highly flexible ASG, a length of 1 m parallel to flow direction provides shelter. ASG mats could thus potentially help to restore seagrass even under harsh conditions (high flow velocities and turbidity), where natural protection structures such as mussel beds are not feasible or where other restoration techniques have previously failed (Talbot and Wilkinson, 2000).…”
Section: Promoting Positive Feedback Mechanisms By the Use Of Artificial Structuresmentioning
confidence: 99%
“…The ASG patch should be large enough to provide the shelter needed against hydrodynamic energy and erosion, but small enough to (a) be economically feasible; (b) not greatly disturb the natural environment (e.g., covering other habitats and reducing nutrient exchange between adjacent areas); and (c) provide enough space and light for seagrass to establish, grow and expand within and beyond the ASG boundaries. The dimensions of the ASG providing this facilitation can be explored in physical experiments in a hydraulic laboratory facility (e.g., a wave flume or basin) with systematic variation of specific parameters (e.g., wave height/length, distance between mats) (Paul and Gillis, 2015;Villanueva et al, 2021). The prototype meadow can vary in canopy height, leaf density and meadow length as well as geometry and mechanical properties of individual stems, in order to control sedimentation and reduction of hydrodynamic energy (e.g., Taphorn et al, 2021).…”
Section: Proposed Approaches For Seagrass Restoration With Artificial Seagrass (Asg) Prototype Designmentioning
confidence: 99%
“…A plethora of pilot seagrass restoration projects have tested different approaches; van Katwijk et al (2016) provide a metaanalysis of more than 1700 trials, concluding that success, defined through seagrass survival, is mainly driven by the number of introduced seedlings and the site selected for restoration. Hydrodynamic conditions, i.e., incident wave heights and currents, also represent an important factor for survival (Barbier et al, 2011), so that shelter of seedlings plays an important role for restoration (Villanueva et al, 2021). To achieve shelter, artificial seagrass (ASG) mats can be deployed in order to minimize wave loading and currents in and around the desired restoration area, subsequently enhancing sedimentation and improving light availability (Carus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%